Time to disease diagnosis in patients with diabetes and arterial hypertension with symptoms of depression in a sample of Peruvian residents. - Loayza-Castro, Joan A.; Vera-Ponce, Víctor Juan (Medicina Clínica y Social, 2024)
Introduction: The prevalence of AHT is between 11.9 % and 49 %, and that of DM2 is 10.5 %. The prevalence of depressive disorders in patients with diabetes ranges from 10 to 15%. Objective: To determine the association between the time of illness in patients with hypertension and DM2 with depressive symptoms. Methodology: This was a cross-sectional analytical study. The secondary base analyzed was the Demographic and Health Survey of Peru (ENDES) for 2019, 2020, and 2021. The Patient Health Questionnaire-9 (PHQ-9) was used. The chi-square test was used for each possible factor associated with depression, and the associations of interest were evaluated using Poisson distribution. Results: At the time of the study, 21.59% of patients had symptoms of depression. Of these patients, 51.40 % were female. A total of 16.58 % of the participants were older than 60 years of age. Hypertension was present in 5.9% of the patients, while DM2 was present in 2.09%. In the bivariate analysis, all variables were associated with the presence of depressive symptoms, except for daily smoking (p=0.275). Discussion: The results showed an association between the time of illness since the diagnosis of HT and DM2 and depressive symptoms. In the case of both pathologies, having less than one year since diagnosis increased the probability of depressive symptoms by 51% and 44%, respectively.
Keywords: Diabetes Mellitus; Arterial Hypertension; Depression; Time